2013
DOI: 10.1007/s12262-013-0876-6
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pneumothorax Recurrence and Surgery

Abstract: Spontaneous pneumothorax that occurs in patients with no underlying lung disease is termed primary spontaneous pneumothorax (PSP). Recurrence of pneumothorax is usually seen without surgical procedures at any time. The aim of this study was to determine the recurrence time and rate of PSP after the first episode. A total of 82 PSP patients who had been treated in a thoracic surgery clinic between March 2011 and August 2012 were studied retrospectively. Video-assisted thoracoscopic surgery (VATS) was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 13 publications
0
12
0
2
Order By: Relevance
“…In the absence of an underlying lung disease, it is termed primary spontaneous pneumothorax (PSP) with an annual incidence of 7.4–37 per 100 000 in men and 1.2–15.4 per 100 000 in women and typically seen among young adults [ 8 , 9 ]. One retrospective study found 23.5% recurrence of PSP within the first 6 months [ 8 ]. The presence of subpleural blebs and bullae is seen in 80–90% of PSP cases.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of an underlying lung disease, it is termed primary spontaneous pneumothorax (PSP) with an annual incidence of 7.4–37 per 100 000 in men and 1.2–15.4 per 100 000 in women and typically seen among young adults [ 8 , 9 ]. One retrospective study found 23.5% recurrence of PSP within the first 6 months [ 8 ]. The presence of subpleural blebs and bullae is seen in 80–90% of PSP cases.…”
Section: Discussionmentioning
confidence: 99%
“…PSP has been advocated to be developing in young males with tall and thin habitus. [1][2][3]5 Moreover, bullous parenchymal lesions and smoking are frequently considered as risk factors for first episode of PSP. [5][6][7][8][9] These arguments only apply to the findings in this study in terms of gender and presence of bulla.…”
Section: Discussionmentioning
confidence: 99%
“…Tall and thin body habitus, male gender and smoking are frequently encountered clinical features while subpleural blebs and bullae appear to play a role in the pathogenesis of PSP at a rate up to 80%. 1,2 Regarding the size of pneumothorax and the clinical presentation of the patients, various treatment modalities including observation, aspiration, chest tube insertion, chemical pleurodesis or surgery can be applied both at the time of the first episode and recurrence. 2 Recurrence rate of PSP is accepted to be ranging over 30% after the first episode.…”
Section: Introductionmentioning
confidence: 99%
“…PSP is a critical clinical problem and several reports have suggested early surgery to decrease the recurrence rate and repeated admission [25,26]. The recurrence risk is about 25% after the first pneumothorax episode and about 70% after the second episode if without adequate managements [2,27].…”
Section: Discussionmentioning
confidence: 99%